POLITICS AND LEADERSHIP FATIGUE IN AFRICA. A THEORETICAL APPRAISAL. - Akani, Christian (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Colonialism cannot be forgotten in Africa because of the disorientation and dissonance it enforced. This scenario paved way for unbridled expropriation of human and material resources. But, by the beginning of the 1940s African nationalists rejected the colonial political economy, and demanded for self governance. The aftermath of their demand engendered a wind of change which swept most African states to statehood in the 1960s. Regrettably, five decades after independence, the continent is still experiencing a free fall in all human development sectors. Those who inherited political power, rather than ensuring inclusive governance have imposed pain and terror on their people . With an analytical , method the paper argues that politics is squarely responsible for the leadership fatigue in the continent. It concludes that for Africa to have the right leaders they desire, the political institutions must guarantee popular participation.